A subareolar breast abscess in a man: A case report and literature review. Issue 6 (December 2020) - Alqahtani, Saad M.
الملخص: يعتبر خراج الثدي تحت الهالة عند الذكور نادرا بشكل استثنائي. حتى اليوم، تم وصف ١٥ حالة فقط لخراج الثدي تحت الهالة عند الذكور في الأدب الإنجليزي. نقدم حالة خراج الثدي تحت الهالة ‏ لرجل يبلغ من العمر ٢٨عاما حضر إلى عيادة الجراحة يشكو من تورم مؤلم في الثدي الأيمن من ١٠ أيام. أظهر الفحص السريري وجود كتلة ساخنة طرية تحت هالة الثدي الأيمن مع احمرار للجلد. وأظهرت الأمواج فوق الصوتية للثدي الأيمن السمات الإشعاعية لخراج الثدي. نتج عن الرشف بالإبرة ‏الدقيقة صديدا بني- أصفر. بناء على هذه النتائج، تم تشخيص خراج تحت هالة حلمة الثدي الأيمن. هذه الحالة هي أول حالة موثقة لخراج الثدي تحت الهالة ‏عند الذكور من المملكة العربية السعودية. إلى جانب ذلك، تقرير هذه الحالة يلقي الضوء على النهج الحالي السريري والعلاجي لعلاج حالات خراج الثدي تحت الهالة عند الذكور. Abstract: Subareolar breast abscesses (SBAs) in men are extremely rare. To date, only 15 men with SBA have been reported in the English literature. We present a case of SBA in a 28-year-old man who visited our surgical clinic with a painful swelling in his right breast for 10 days. Physical examination showed a tender, hot mass in the right subareolar area with erythema. Ultrasound of the right breast showed radiological features of a breast abscess. Fine-needle aspiration yielded brownish yellow pus. Based on these findings, a diagnosis of right SBA was established. This is the first documented case of SBA in men from the KSA. Additionally, this case report sheds light on the current clinical and therapeutic approaches to managing cases of SBA in men.